2021
DOI: 10.1111/sdi.13001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of mortality and complications between urgent‐start peritoneal dialysis and urgent‐start hemodialysis: A systematic review and meta‐analysis

Abstract: The advantages of urgent‐start peritoneal dialysis (PD) vis‐à‐vis urgent‐start hemodialysis (HD) are not clear. We performed a systematic review and meta‐analysis of studies comparing the two modalities. Databases of PubMed, Embase, Ovoid, and Google Scholar were searched up to November 1, 2020. The primary outcome was mortality, and secondary outcomes were dialysis‐related infectious complications and mechanical complications. Risk ratios (RRs) were calculated for all outcomes. Seven studies were included. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…However, this delay has led to a low adoption rate of PD and left many patients without a viable dialysis plan, relegating them to HD. With the recent progress in PD catheter insertion technique, urgent-start PD is now a comparable and even superior option when compared to urgent-start HD via a central vein catheter [22,25]. We here demonstrate that the hybrid PD catheter insertion approach is a secure and effective option for prompt initiation of PD in ESKD patients.…”
Section: Discussionmentioning
confidence: 71%
“…However, this delay has led to a low adoption rate of PD and left many patients without a viable dialysis plan, relegating them to HD. With the recent progress in PD catheter insertion technique, urgent-start PD is now a comparable and even superior option when compared to urgent-start HD via a central vein catheter [22,25]. We here demonstrate that the hybrid PD catheter insertion approach is a secure and effective option for prompt initiation of PD in ESKD patients.…”
Section: Discussionmentioning
confidence: 71%
“…Ding et al [35] recently published a systematic review and meta-analysis of seven studies comparing urgentstart PD with urgent-start HD, with mortality as the primary outcome, and dialysis-related infectious complications and mechanical complications as secondary outcomes. Their pooled analysis showed a significantly reduced risk of all-cause mortality in patients on urgentstart PD as compared to urgent-start HD.…”
Section: Discussionmentioning
confidence: 99%
“…b Patients with peritoneal dialysis could not include analysis due to hemodialysis modality specific variable (n = 100). [18]. Dias et al found that the frequency of catheterrelated bacteremia and mechanical complications were 24.1% and 37.4% in patients with urgent-start HD [7].…”
Section: Discussionmentioning
confidence: 99%
“…Another meta‐analysis conducted in 2021 revealed that observational studies indicate lower mortality and lower risk of mechanical complications with urgent‐start PD versus urgent‐start HD. They also found that the risk of infectious complications was not different between the two dialysis modalities in contrast to Htay's meta‐analysis [18]. Dias et al found that the frequency of catheter‐related bacteremia and mechanical complications were 24.1% and 37.4% in patients with urgent‐start HD [7].…”
Section: Discussionmentioning
confidence: 99%